Kompetensi Profesional Guru dalam Meningkatkan Mutu Pendidikan di SMA Negeri 1 Sidayu - Rosilawati, Rosilawati; Ansori, Aristawidya Salsabila; Cindy, Agustin Hanivia; Windasari, Windasari (TSAQOFAH, 2024)
This study discusses the role of teachers' professional competence in improving the quality of education at SMA Negeri 1 Sidayu. The research was conducted by analyzing teacher competency development strategies and their impact on the learning process. The research method used is qualitative and includes observation, interviews and analysis of related documents. The results showed that teachers' professional competence is very important in shaping a competent and qualified young generation. Teachers at SMA Negeri 1 Sidayu apply various innovative learning methods, such as question and answer, hands-on practicum, and independent curriculum-based projects. In addition, the principal also plays a crucial role in developing teachers' competencies through classroom supervision programs and professional coaching. By improving teachers' competencies, it is expected that the quality of education at SMA Negeri 1 Sidayu can be continuously improved to create an optimal learning environment for students.